Evaluation of Commercial and Candidate Bread Wheat Varieties for Durable Resistance to Rusts in Pakistan: Short Communication - Shah, Syed Jawad Ahmad; Muhammad, Tila; Azam, Farooq-e (Biological Sciences - PJSIR, 2005)
Commercial and candidate bread wheat varieties were evaluated for durable resistance to rusts. The candi- date varieties included genotype lines from the National Uniform Wheat Yield Trial, including Rainfed, Normal and Short trial programmes. A total of 89 genotype entries were evaluated. The evaluation was done on the basis of well recognized visual phenotype marker, the adult plant leaf tip necrosis. It was noted that 64% of the genotype varieties expressed this phenotype marker